Quality Management System at The University of Nizwa, Sultanate of Oman - Waleed A. Thanoon; Ahmed K.; Abul Aziz Al Kindy; Rose Bahou (University of Science and Technology, Yemen, 2014)
Abstract:  The competition between Higher Education Institutions (HEIs) and growing mandates for accountability by national and international accreditation associations, funding bodies are among the reasons behind the growing needs to focus on quality for higher education providers. Hence, the major concern among the HEIs is to implement Quality Management. The UoN adopted the European Foundation for Quality Management (EFQM) Excellence Model. Total Quality Management "TQM" has been championed at all levels of the University of Nizwa. The Board of Trustees has been responsible for overseeing the fulfillment of the vision, mission and core values. The University Academic Council evaluates all academic processes, and directs units to means of enhancement. The University Executive Board and the Deanship for Academic Excellence and Quality Management oversee adherence (consistent implementation) to quality at all levels, while all faculty contribute to Quality management through institutionalization. The UoN has developed a comprehensive pedagogic framework called "Quality Teaching Management System" (QTMS) to manage the quality of student teaching and learning and assessing student's performance. The system includes the teaching procedure, the role of faculty and students, responsibilities of the Head of Department, Deanship of Registration & Records, the Dean, and quality management on the implementation of teaching at the UoN. Applying TQM at the institution will add great value to educational framework benefiting all stakeholders and in the end the graduate.  Embracing TQM will become intertwined within the university culture which in turn will be reflected in the graduate attributes and society satisfaction. Keywords: Teaching & Learning, Total Quality Management, Higher Learning Institution, University of Nizwa, Sultanate of Oman.